133k views
4 votes
Rewrite the expression with rational exponents as a radical expression by extending the properties of i tiger exponents

Rewrite the expression with rational exponents as a radical expression by extending-example-1
User Jinho Yoo
by
5.8k points

1 Answer

3 votes

Answer:


\sqrt[6]{y}

Explanation:

The expression is


\frac{y^{(1)/(3) } }{y^{(1)/(6)}}

Applying rule of exponents,
(x^(m))/(x^(n))=x^(m-n)


\frac{y^{(1)/(3) } }{y^{(1)/(6)}}=y^{(1)/(3)-(1)/(6)}=y^{(2-1)/(6)}=y^{(1)/(6)}

Now,we know that,
x^{(1)/(n)}=\sqrt[n]{x}


y^{(1)/(6)}=\sqrt[6]{y}

So, the last option is correct.

User Pavel Alazankin
by
5.4k points